2021
DOI: 10.1186/s12888-021-03484-9
|View full text |Cite
|
Sign up to set email alerts
|

The attitudes of psychiatric patients towards COVID-19 vaccination in China: a cross-sectional study

Abstract: Background The COVID-19 pandemic has become a global health catastrophe. By far, there has been no specific antiviral treatment for COVID-19. Developing a vaccine against COVID-19 appeared to be the most cost-effective strategy to stop the repeated outbreak. This study aimed to investigate the attitudes of psychiatric patients with regards to COVID-19 vaccination and potential factors that might influence their decision-making process. Methods Psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
0
13
0
1
Order By: Relevance
“…Better mental health in Facebook users was associated with worse attitude and behaviour, while worse mental health in Twitter users was associated with better attitude and behaviour. This was common in several studies showing that psychiatric disorders were positively affecting the decision of vaccination [39,40]. This finding was unexpected in all studies.…”
Section: Discussionmentioning
confidence: 58%
“…Better mental health in Facebook users was associated with worse attitude and behaviour, while worse mental health in Twitter users was associated with better attitude and behaviour. This was common in several studies showing that psychiatric disorders were positively affecting the decision of vaccination [39,40]. This finding was unexpected in all studies.…”
Section: Discussionmentioning
confidence: 58%
“…Contrarily, a recent Chinese cross-sectional study revealed that 83.3% of the Chinese psychiatric patients preferred Chinese vaccines which are of inactivated virus, protein subunit, and viral vector-based types. In comparison, only 16.7% preferred the imported vaccines, including mRNA-based vaccines, thus reflecting the crisis of vaccine nationalism [58].…”
Section: Discussionmentioning
confidence: 99%
“…One study found a slightly lower willingness to be vaccinated when compared to the general population, although the difference was rather small ( 17 ). In a Chinese survey only 78.7% of patients and family members intended to receive a vaccine ( 33 ). Another small study in a medium security psychiatric hospital showed that 20% of patients declined consent to be vaccinated ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Large parts of the world are unfortunately still waiting for the chance at a first vaccine shot. To ensure maximal vaccine uptake healthcare providers and policy makers should provide enough information on vaccine safety, individual risk assessment and explicitly recommend vaccination as support from healthcare providers increases chance of vaccination ( 33 , 34 , 36 , 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%